The implementation of collaborative-based guided discovery reviewed from students’ analytical thinking skills and social skills - Anwari Adi Nugroho (Jurnal Inovasi Pendidikan IPA, 2017)
This study aimed to determine the effectiveness of collaborative based Guided Discovery in empowering critical thinking skills and social skills of students in High Plant Systematics Course. It was a quasi-experimental study with One Group Pretest-Posttest Design using one class as an experiment (pretest and posttest). The subjects of the study were 26 students of the fourth semester of Department of Biology Education, Universitas Bangun Nusantara Sukoharjo Academic Year 2015/2016. Data collection techniques were done with tests to measure analytical thinking skills and observation to measure social skills. Data analysis of the result of analytical thinking skills was quantitative descriptive using paired sample t-test, while the result of social skill observation was qualitative descriptive. Paired sample t-test resulted in a significant difference of pretest and posttest value of analytical thinking skill. The result of social skill score was nine students with very good category and seventeen students with a good category. The conclusion of the study was that collaborative based Guided Discovery effectively empowers the student’s analytical thinking and social skills.